SINTESIS Zn(II)/SILIKA DENGAN METODE SOL-GEL SEBAGAI BAHAN ANTIBAKTERI Esherichia coli DAN Staphylococcus aureus - , DIAN ANGGRAINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Synthesis of Zn(II)/silica by sol-gel method as antibacterial material against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus) has been done. Sol-gel process was carried out by reacting tetraethoxysilane, H2O, HCl, ethylene glycol and ZnCl2. The ZnCl2 concentrations varied 0.25, 0.5